Hi everyone,

Need help to verify this working.Thank you for all help & support.

Find $\displaystyle \frac{dz}{dx}$ & $\displaystyle \frac{dz}{dy}$ for

$\displaystyle x^2y^3z+yz^2-xy=0$

$\displaystyle 2xy^3z+x^2y^3\frac{dz}{dx}+2yz\frac{dz}{dx}-y=0$

$\displaystyle (x^2y^3+2yz)\frac{dz}{dx}=y-2xy^3z$

$\displaystyle \frac{dz}{dx}=\frac{y-2xy^3z}{x^2y^3+2yz}$

$\displaystyle 3x^2y^2z+x^2y^3\frac{dz}{dy}+z^2+2yz\frac{dz}{dy}-x=0$

$\displaystyle \frac{dz}{dy}=\frac{x-3x^2y^2z-z^2}{x^2y^3+2yz}$

Thank you in advance for all help & support,really appreciate.